The earliest beetle with mouthparts specialized for feeding on nectar is a parasitoid of mid-Cretaceous Hymenoptera - Jan Batelka (BMC, 2021)
Abstract Background During the Mesozoic, there were many insects in several holometabolous orders (Neuroptera, Mecoptera and Diptera) with elongated mouthparts adapted for feeding on nectar. The evolutionary history of the megadiverse order Coleptera, which has a great diversity of mouthparts and feeding strategies, is well documented since early Permian with a significant peak in diversity in the Triassic. Currently, however, there is no evidence that in the Mesozoic these beetles fed on nectar despite the recorded specializations for pollination of flowering plants in several families since the mid-Cretaceous. Results Here we describe a new wedge-shaped beetle Melanosiagon serraticornis gen. et sp. nov. from mid-Cretaceous Burmese amber attributed to Macrosiagonini (Ripiphoridae: Ripiphorinae), which has elongated galea comparable to that in the extant parasitoid genus Macrosiagon, and a well known example of adaptation for nectar feeding in Coleoptera. Furthermore, Salignacicola gen. nov. is established for Macrosiagon ebboi Perrichot, Nel et Néraudeau, 2004, based on the holotype found in mid-Cretaceous amber from France. Systematic positions of both newly established genera are discussed. A list of potential wasp and bee hosts of Ripiphorinae from the Mesozoic is provided. Conclusions This study presents evidence of the earliest occurrence of specialized nectar feeding mouthparts in Coleoptera. Melanosiagon serraticornis is closely related to extant Macrosiagonini. In all genera belonging to subfamily Ripiphorinae the primary larvae are adapted for parasitism on aculeate Hymenoptera (bees and wasps) and adults are associated with blossoms of flowering plants, in terms of their specialized morphology. Adults of Macrosiagon visit blossoms of flowering plants to obtain nectar and lay eggs from which the hatching larvae attack visiting wasps and bees. An association with flowers of some tropical trees is already corroborated in some extant species. Interestingly the larvae of Ripiphorinae are also found in Burmese amber. Thus, both life stages of the mid-Cretaceous Ripiphorinae indicate a close association of this lineage with flowering trees.